2020
DOI: 10.3892/ol.2020.11276
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of metabolic parameters at 18F‑fluorodeoxyglucose positron emission tomography in predicting malignant potential of anterior mediastinal tumors

Abstract: To evaluate the utility of 18 F-fluorodeoxyglucose (FDG)-positron emission tomography (PET) for predicting the malignancy of anterior mediastinal tumors, the present study retrospectively examined a total of 105 consecutive patients who underwent surgical resection of anterior mediastinal tumors at Gunma University Hospital after undergoing a preoperative FDG-PET scan. Patients were divided into benign and malignant groups in accordance with the following three classification systems: i) Clinical classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Numerous studies reported the utility of PET for the diagnosis of malignant anterior mediastinal tumors (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Due to increased glucose metabolism, malignant tissues typically demonstrate higher FDG uptake compared with benign and normal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies reported the utility of PET for the diagnosis of malignant anterior mediastinal tumors (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Due to increased glucose metabolism, malignant tissues typically demonstrate higher FDG uptake compared with benign and normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of PET for the clinical diagnosis of malignant tumors, including thymoma and thymic cancer, has been reported in numerous publications (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Fluorodeoxyglucose (FDG) accumulation in high-risk thymoma, particularly thymic carcinoma, is evidently greater compared with in low-risk thymoma (10)(11)(12)(13)(14)(15)(16)(17)(18)20). The role of fluorodeoxyglucose-positron emission tomography (FDG-PET) in differentiating benign and malignant thymic masses has been previously evaluated by several small-scale studies (21).…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have described the 18 F-FDG PET or PET/CT values in the diagnosis of mediastinal tumors, to our knowledge, most studies have analyzed some types of these tumors [ 17 , 20 22 ],and there were few systematic descriptions of thymic tumors and comparisons between TETs and thymic lymphomas [ 23 ]. Most studies only rely on PET metabolic parameters for analysis, ignoring the differences in patients’ baseline characteristics and clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have described the 18 F-FDG PET or PET/CT values in the diagnosis of mediastinal tumors, to our knowledge, most studies have analyzed some types of these tumors [17,[20][21][22],and there were few systematic descriptions of thymic tumors and comparisons between TETs and thymic lymphomas [23].…”
Section: Introductionmentioning
confidence: 99%